2022
DOI: 10.1051/0004-6361/202140747
|View full text |Cite
|
Sign up to set email alerts
|

Overall spectral properties of prompt emissions with diverse segments inSwift/BAT short gamma-ray bursts

Abstract: Owing to a lack of multiple components of prompt γ-ray emissions in short gamma-ray bursts (sGRBs), how these distinct components are correlated remains unclear. In this paper we investigate the spectral and temporal properties of precursors, main peaks, and extended emissions in 26 sGRBs including GRB 170817A. It has been found that peak energies (Ep) in each pulse are uncorrelated with the pulse duration (tdur). Meanwhile, we find that there is no obvious correlation between peak energy and energy fluence. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…LGRBs and 93 SGRBs as our data set III. The traditional S/N > 3 criterion in each time bin has been adopted to distinguish the EE segments (see, e.g., von Kienlin et al 2019;Li et al 2021aLi et al , 2022, which is slightly different from the results in the literature (Zhang et al 2016;Kisaka et al 2017;Yu et al 2020;. It is noticeable that the ratio of short to long GRBs remains almost unchanged after these EE GRBs are excluded.…”
Section: Samplementioning
confidence: 90%
“…LGRBs and 93 SGRBs as our data set III. The traditional S/N > 3 criterion in each time bin has been adopted to distinguish the EE segments (see, e.g., von Kienlin et al 2019;Li et al 2021aLi et al , 2022, which is slightly different from the results in the literature (Zhang et al 2016;Kisaka et al 2017;Yu et al 2020;. It is noticeable that the ratio of short to long GRBs remains almost unchanged after these EE GRBs are excluded.…”
Section: Samplementioning
confidence: 90%
“…We take two steps to obtain the more accurate spectral lags. First, in order to obtain the smooth CCF curves, we follow Zhang et al (2006aZhang et al ( , 2006b to fit the light-curve data using the "KRL" function of individual GRB pulses and obtain four smooth light-curve pulses (Li et al 2020(Li et al , 2021a(Li et al , 2022a. Then, we perform the CCF analysis with the Stingray Python package (Huppenkothen et al 2019b(Huppenkothen et al , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that the precursor, the main burst, and the extended emission have the same physical origin. Li et al (2022) studied the precursors of LGRBs, and the temporal behavior of the precursor is similar to that of the main burst. In our work, it is shown that the precursor, the main emission, and the extended emission are dominated by the thermal emission.…”
Section: Discussionmentioning
confidence: 99%